Extração com fluido supercrítico e extração assistida por ultrassom na obtenção de compostos antioxidantes produzidos por Diaporthe schini - Rosa, Barbara Vargas da (2020)
The Pampa biome that covers southern Brazil and part of Uruguay and Argentina has one of the richest biodiversity in the world, which has not yet fully described by science. Part of this biodiversity are the endophytic fungus, being exploited for the production of metabolites with different bioactive properties. One of these properties is the ability of a molecule to protect against attack by free radicals, providing interesting several segments such as the food, and pharmaceutical industries. Therefore, the main objective of this work was to extract antioxidant compounds from the biomass obtained from the fermentation of endophytic fungus Diaporthe schini using supercritical fluid extraction (SFE) and ultrasound-assisted extraction (UAE). The extraction using carbon dioxide (CO2) in the supercritical state was performed using pure CO2 and CO2 plus ethanol as cosolvent. For the supercritical extractions pressure (150-250 bar), temperature (40-60 ºC) and cosolvent [biomass: cosolvent ratio, 1:0, 1:0.75 and 1:1.5 (w/v)] were evaluated. According to experimental data, kinetic curves and mass transfer rates, the best condition was obtained using 250 bar, 40 ºC and biomass: cosolvent ratio of 1:1.5 (w/v), with extraction yield and the antioxidant activity against the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical of 3.24 % e 96.62 %, respectively. The ultrasound-assisted extraction was performed using ethanol as solvent and the parameters ultrasound intensity (17-85 W.cm-2) and pulse cycle (0.50-1.00) were investigated according to a Central Composite Rotatable Design (CCRD), to obtain a highest extract yield. The validation condition was performed using an ultrasound intensity of 85 W.cm-2 and a pulse cycle of 0.93, resulting in an extraction yield of 22.30 ± 0.47 % and an antioxidant activity of 91.35 ± 0.27 %. The heat-assisted extraction which was performed for comparison, presented an extract yield of 8.34 ± 0.38 % and an antioxidant activity of 91.32 ± 0.89 %. Analysis of the extracts by gas chromatography/ mass spectroscopy (GC/MS) indicated the presence of the compounds 1,4-diaza-2,5- dioxo-3-isobutyl bicyclo[4.3.0]nonane, benzeneethanol, 9,12 octadecadienoic acid (Z, Z), methyl ester, hexadecanoic acid, and ethyl octadec-9-enoate which could be attributed to the antioxidant activity found in this study. The results demonstrated that supercritical fluid extraction was more selective, due to the greater antioxidant activity in relation to the other extraction methods evaluated. However, in the ultrasound-assisted extraction, the yield was higher, the extraction time was reduced, keeping the antioxidant activity high, thus being the most interesting method.